Teaching mathematical literacy - Moses, Robert; Fifth International Teaching for Intelligence Conference (Washington : SkyLight Professional Development, 1999)
Robert Moses stresses teaching of mathematics to disadvantaged students as a critical step in altering low expectant practices in urban classrooms
Executive producer, Robert Moses
Keywords: Mathematics -- Study and teaching